2002
DOI: 10.1093/ije/31.3.624
|View full text |Cite
|
Sign up to set email alerts
|

Relation of adult lifestyle and socioeconomic factors to the prevalence of Helicobacter pylori infection

Abstract: Male gender, living with a partner and poor adult socioeconomic conditions are associated with increased risk of H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
95
8
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 23 publications
21
95
8
3
Order By: Relevance
“…Factors linked to household conditions, such as present family size, were not relevant determinants of H. pylori infection status in this adult population, a finding also observed by others, both in developed and in developing countries. In most of these studies, a clear association was seen between socioeconomic status and overcrowding in childhood, but not with present household conditions [21,22,11]. Although we did not evaluate socioeconomic status and overcrowding during the childhood of the subjects involved in this survey, we had previously demonstrated that 75.4% of the children living in this community were infected.…”
Section: Discussionmentioning
confidence: 86%
“…Factors linked to household conditions, such as present family size, were not relevant determinants of H. pylori infection status in this adult population, a finding also observed by others, both in developed and in developing countries. In most of these studies, a clear association was seen between socioeconomic status and overcrowding in childhood, but not with present household conditions [21,22,11]. Although we did not evaluate socioeconomic status and overcrowding during the childhood of the subjects involved in this survey, we had previously demonstrated that 75.4% of the children living in this community were infected.…”
Section: Discussionmentioning
confidence: 86%
“…However, there is lack of consensus on the association between H pylori prevalence and some of these factors such as age and gender. Even though recent epidemiological studies report an age-dependent increase in H pylori positivity, various studies describe that the prevalence of H pylori infection does not differ with age (Graham et al, 1991;The EUROGAST Study Group., 1993;Moayyedi et al, 2002;Rodrigues et al, 2005). Similar controversies exist on the association between H pylori positivity and gender.…”
Section: Discussionmentioning
confidence: 96%
“…Although, another study conducted by Moges et al demonstrated that H. Pylori infection is related to alcohol abuse (Moges et al, 2006) but due to cultural and religious reasons we did not asked about the use of alcohol by study participants. Literature reveals that H. Pylori infection is more prevalent in children and younger ages (Moayyedi et al, 2002). In our study also H. Pylori infection is more prevalent among patients with young age.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that 50% adult in developed countries and 90% adults in developing countries were positive of serum antibodies against H. pylori (Wu et al, 2003). The critical period at which H. pylori is acquired, is during the childhood, especially in the developing countries and areas of overcrowding and socioeconomic deprivation (Moayyedi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation